After the financial crisis: Reforms and reform options for finance, regulation and institutional structure - Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
The finance dominated type of capitalism that has developed from the late 1970s and early 1980s on finds its nucleus in the deregulation of the national and international financial system and the switch to a shareholder oriented corporate governance system. Other aspects such as labour market deregulations (including policies to weaken trade unions), the aim of completely free trade around the globe, increasing freedom and power of multinational companies, and privatisation of formerly state functions also belong to the new regime. This finance dominated economic regime seems to be exhausted. The reforms implemented after the subprime crisis and the Great Recession are not sufficient to overcome the deeply rooted problems of the existing system. Reforms to the financial system did not substantially affect the functioning of the shadow banking system and the basic structures of the financial system were not changed. Both, the international financial system as well as the shareholder oriented corporate governance system were largely spared from reforms. Further labour market deregulations are still on the agenda of governments and international institutions. Policies to change income and wealth distribution are not on the political agenda. What is needed is a comprehensive reform agenda which searches for a new relationship between institutions, government policies, and markets.
Keywords: E12; E44; F33; G28; P10; 330; financialisation; financial market regulation; demand management; income distribution